1987
DOI: 10.1016/s0006-3495(87)83274-5
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman studies of sterically hindered cyanomet "strapped" hemes. Effects of ligand distortion and base tension on iron-carbon bond

Abstract: We report resonance Raman studies of the iron-carbon bond stretching vibrations, nu(Fe-CN), in sterically hindered and unhindered heme (FeIII)-CN- complexes. The sterically hindred "strapped hemes" are equipped with a covalently linked 13-, 14-, or 15-atom hydrocarbon chain across one face of the heme; these are called FeSP-13, FeSP-14, and FeSP-15, respectively. These straps would presumably exert a sideway shearing strain to force the linear ligands (e.g., CN- and CO) to be tilted and/or bent. The shorter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Increases in these ν Fe−C frequencies have been attributed to removal of constraints on the FeCN unit based on "strapped" heme cyanide model complexes with (CH 2 ) n chains over the heme, where lengthening or eliminating the strap hindering the bound CN − caused the ν Fe−C to shift to higher frequencies (n = 13− 15, 445−447 cm −1 ; no strap, 451 cm −1 ). 78 A similar trend is observed in heme protein cyanide complexes. For example, the crystal structure of Chlamydomonas Hb−CN − (PDB entry 1DLY) revealed that its FeCN angle is 130°due to a Hbonding network involving a Tyr and two Gln residues in its distal pocket.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Increases in these ν Fe−C frequencies have been attributed to removal of constraints on the FeCN unit based on "strapped" heme cyanide model complexes with (CH 2 ) n chains over the heme, where lengthening or eliminating the strap hindering the bound CN − caused the ν Fe−C to shift to higher frequencies (n = 13− 15, 445−447 cm −1 ; no strap, 451 cm −1 ). 78 A similar trend is observed in heme protein cyanide complexes. For example, the crystal structure of Chlamydomonas Hb−CN − (PDB entry 1DLY) revealed that its FeCN angle is 130°due to a Hbonding network involving a Tyr and two Gln residues in its distal pocket.…”
supporting
confidence: 64%
“…Interestingly, several heme proteins having a distal Gln residue exhibit ν Fe–C frequencies comparable to those of the three Cld–CN – complexes reported here (Table ). Increases in these ν Fe–C frequencies have been attributed to removal of constraints on the FeCN unit based on “strapped” heme cyanide model complexes with (CH 2 ) n chains over the heme, where lengthening or eliminating the strap hindering the bound CN – caused the ν Fe–C to shift to higher frequencies ( n = 13–15, 445–447 cm –1 ; no strap, 451 cm –1 ) . A similar trend is observed in heme protein cyanide complexes.…”
Section: Discussionmentioning
confidence: 63%
“…The additional smaller difference patterns observed in this region arise probably from the vibrational coupling of the δ(Fe–CN) bending mode with the in-plane porphyrin skeletal modes of E u geometry, as reported previously. 12 , 15 …”
Section: Resultsmentioning
confidence: 99%
“… 12 However, in heme proteins, the CN – ligand interacts with the active site amino acid residues, and the presence of steric or polar interactions can induce a conformational change of the Fe–C≡N fragment. 14 , 15 The Fe–C≡N linkage can adopt tilted linear (also called “essentially linear”) or bent geometries, depending on the nature of steric and/or H-bonding interactions. 14 16 The high sensitivity and responsiveness of the Fe–C≡N linkage to the heme pocket environment make cyanide ligands an excellent probe of the active site structure.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was found that the stronger the trans ligand, the weaker the Fe"-CO bond (2). However, the relation of this trans effect is reversed in cyanomet Fe"' heme systems, i.e., the v(Fe"'-CN) frequency increases the increasing donor strength of the trans ligand (17). The origin of these effects might be due to different extents of the dj(M) X 7r* (XO) backbonding.…”
Section: !mentioning
confidence: 98%